The ARTISTIC Online Calculator: Exploring the Impact of Lithium‐Ion Battery Electrode Manufacturing Parameters Interactively Through Your Browser. Issue 3 (27th January 2022) - Lombardo, Teo; Caro, Fernando; Ngandjong, Alain C.; Hoock, Jean‐Baptiste; Duquesnoy, Marc; Delepine, Jean Charles; Ponchelet, Adrien; Doison, Sylvain; Franco, Alejandro A.
Abstract: This article presents the ARTISTIC online calculator, a web platform that enables both experimental and computational researchers to access the ARTISTIC project three‐dimensional (3D) manufacturing models. This platform is free of charge and utilizes a user‐friendly interface to guide users among the different manufacturing steps and their parameters. The current version of the online calculator accounts for the slurry phase, its drying, and electrode calendering; it gives access to a variety of relevant parameters, as slurry solid content, electrode formulation, particle size distribution, and drying/calendering conditions. To utilize this platform, the user should simply register freely to the ARTISTIC computational portal, select the manufacturing parameters of interest, and launch the simulations through the user‐friendly interface. As soon as the simulation ends, the user who launched it receives an email with the links to visualize and recover the resulting electrode/slurry microstructure. Furthermore, all the results obtained through this platform are shared among all the users, i. e., everyone can visualize and recover all the microstructures available. Therefore, this platform also constitutes an open‐access database linking manufacturing conditions and simulated electrode microstructures. In addition, these microstructures can be embedded straightforwardly in electrochemical models. In brief, we hope that the battery community will see this online platform as a tool to explore the vast manufacturing parameter space accessible through our 3D models and to establish a deeper knowledge of the manufacturing‐microstructure‐electrochemistry relationships in a collaborative and fully transparent way. Abstract : Introducing a free online modeling platform : This article presents the ARTISTIC online calculator, a free online platform utilizing a user‐friendly interface and giving access to three‐dimensional (3D) manufacturing models accounting for the slurry phase, its drying, and electrode calendering. The results obtained through this platform are shared among all the users, making it an open‐access database linking manufacturing conditions and 3D electrode microstructures.